Pengaruh Capital Requirements, Kepemilikan Manajerial Terhadap Manajemen Laba yang Dimoderasi Oleh Mekanisme Tata Kelola - Herlina Lusmeida; Khomsiyah Khomsiyah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study is to examine the effect of capital requirements on earnings management as well as the effect of managerial ownership on earnings management, besides that this study also wants to examine the governance mechanisms proxied by independent commissioners whether they are able to moderate the effect of each of these variables on earnings management. The sample used was 33 banking companies listed on the IDX for the 2015-2019 period, using panel data and processed using the EViews 9 software. The results of the research show that capital adequacy has a positive effect on earnings management, and governance mechanisms moderate the positive relationship between capital adequacy. to earnings management